Static & Dynamic Analysis of Open Coil Helical Spring used in Two Wheeler Application - Shakya, Vikas; Verma, Dr, P.L.; Agarwal, Dr. Pankaj; Chourasia, Anil (Innovative Research Thoughts, 2024)
In this paper suspension spring of a 160cc 2-wheeler is analyzed and ptimized for its performance. For this study the diameter and the material of the coil ire for suspension is changed and its effect is noted. In this study three materials ere studied that is ASTM A227 hard drawn spring steel material, carbon fibre aterial and titanium alloy. The results were obtained for all of these materials and ased on the results it can be said that spring made of carbon fibre material gives the est results. The springs were tested under both static as well as dynamic loading, and n all of the tests Carbon fibre spring proved to be best.